Penanganan Kesehatan Pasien Reaktif COVID-19 Melalui Terapi Zikir Dan Lingkungan Wawasan Pengalaman Subyektif - Fattah Hidayat; Imam Hidayat; Abdul Ghofur; F. Setiawan Santoso (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2021)
This study describes community action research on the health problems of the santri family due to the impact of COVID 19 in the mosque environment at the neighborhood level of Malang residents. Community action research was carried out using simple ingredients to increase physical immunity so that the effects of disease caused by the COVID 19 virus could be reduced by self-medication. The santri families who have been positively exposed are isolated and consume simple ingredients to vomit and / or have diarrhea so that the santri family is healthy again. The health model of a simple herb is to return an imbalanced body condition back into balance through self-medication so that the family experiences pleasant subjective experiences.